Mismatch unemployment: Evidence from Germany, 2000 - 2010 - Anja Bauer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
This paper provides detailed empirical evidence on the scope of mismatch in Germany in the past decade, using a comprehensive administrative data set that allows for disaggregation at the levels of industry, occupation and region. The findings suggest that regional mismatch did not play an important role in explaining movements of aggregate unemployment. Across industries and occupations, there was a decrease in mismatch unemployment from over 5 percent to below 4 percent (on the highest disaggregation level), whereas the share of mismatch unemployment (across industries and occupations) within total unemployment remains almost unchanged between 2000 and 2010. Concluding, mismatch unemployment fell but the Hartz reforms did not reduce mismatch overproportionally compared with search frictions, in line with the fact that reallocation across occupations appears not to have been eased. – – In diesem Papier wird das Ausmaß der Mismatch-Arbeitslosigkeit mittels eines umfangreichen administrativen Datensatzes, durch welchen Industrien, Berufe und Regionen in unterschiedlichen Disaggregationsstufen analysiert werden können, quantifiziert. Regionaler Mismatch spielt eine untergeordnete Rolle für die Entwicklung der Arbeitslosenquote in Deutschland. Auf Industrie- und Berufsebene kann festgestellt werden, dass die Mismatch-Arbeitslosenquote von über 5% auf unter 4% fällt (auf der detailliertesten Disaggregationsstufe), aber der Anteil der Mismatch-Arbeitslosigkeit an der aggregierten Arbeitslosenquote in der Beobachtungsperiode von 2000 bis 2010 nahezu unverändert bleibt. Zusammenfassend lässt sich sagen, dass die Mismatch-Arbeitslosigkeit zwar gefallen ist, aber nicht überproportional verglichen mit den Suchfriktionen, da die Reformen u.a. berufliche Reallokationsprozesse nicht beschleunigen konnten.
Keywords: E24; J6; 330; mismatch; unemployment; reallocation; panel data